Model-Based Waste Management Handling Angkuts Application to Smart City: The Perspective of Human Security (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Security today is not only defined from a military standpoint, but also human security in which it has relations to social issues, human rights, economic, and environmental. Environmental issues, one of which is on the management of waste handling. A large amount of waste that goes to the place of final processing Pontianak Batu Layang is Hundreds of tonnes per day to make some millennials led by Muhammad Hafiz Waliyyudin initiating Angkuts application to support the city of Pontianak in waste management. This research used a descriptive method for designing a management model, especially waste management planning and actualization of Angkuts towards application-based Smart City from the perspective of human security. Based on these results, the researchers concluded that the design of waste handling management is done through planning and actuating. Planning applications applied technologies based on Angkuts industrial era 4.0 toward achieving smart city. Implementation of an application-based waste handling management Angkuts millennial generation is through participation and government support. As a recommendation, the application has the potential to support Angkuts based waste handling applications in the human security perspective to be used in a wider area again, not only in the city of Pontianak.